Microstructure analysis of tungsten carbide hardfacing on carbon steel blade - Nagentrau, M.; Mohd Tobi, A.L.; Kamdi, Z.; Ismail, M. I.; Sambu, M. (IOP Publishing, 2017)
Tungsten carbide (WC) hardfacing coating is commonly used to enhance carbon steel blade performance which works in acidic and abrasive condition during production process. This paper deals with tungsten carbide (WC) hardfacing microstructure analysis on a carbon steel blade. Mixing of ilmenite ore with sulphuric acid is performed by the carbon steel blade as part of a production process. Tungsten carbide hardfacing is deposited on the carbon steel blade to enhance its wear resistance. The carbide distribution along with elemental composition analysis of the hardfaced carbon steel blade specimens is examined using Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS) and X-Ray Diffraction (XRD) respectively. Microstructure analysis revealed that different sizes of carbides with non-uniform distribution are found around the coating region. The carbide region is contains high percentage of tungsten (W) meanwhile, non-carbide region rich in tungsten (W) and iron (Fe).